The overview analysis of the movie Sense and Sensibility - Nyak Mutia Ismail; Moriyanti Moriyanti (Universitas Islam Sultan Agung, 2019)
Movies have been everybody’s favorite across all ages. Some movies are not suitable for certain ages and the parents’ assistance is needed during the watching movie process so that they can show the morals conceived in the movie. This study tries to shed lights on the elements contained in a movie entitled “Sense and Sensibility”, a movie made based on a novel by Jane Austen. This study was carried out in qualitative approach using visual feature analysis technique. The object of this study was the movie with the duration of 140 minutes. The data obtained were then classified based on its elements such as realism, local color, narratives, and symbolism. The result portrayed that the realism given in this movie is the condition of a noble family who had lost all of their wealth and life had been becoming crude. The local color depicts the social status in the mid-eighteenth century. The story was narrated in the linear plot and finally, the symbolism in this movie exposed much about the calming and melancholic nature of Devonshire.